2007
DOI: 10.1161/circulationaha.107.690487
|View full text |Cite
|
Sign up to set email alerts
|

Role of Neuregulin-1/ErbB Signaling in Cardiovascular Physiology and Disease

Abstract: Abstract-Since the discovery that neuregulin-1 (NRG-1)/ErbB signaling is indispensable in cardiac development, evidence has shown that this system also plays a crucial role in the adult heart. In patients, an inhibitory ErbB2 antibody, trastuzumab, used in the treatment of mammary carcinomas, increases the risk for the development of cardiotoxic cardiomyopathy. Postnatal disruption of NRG-1/ErbB signaling by gene targeting in mice leads to dilated cardiomyopathy. Initially, the search for the mechanisms behind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
210
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 238 publications
(213 citation statements)
references
References 55 publications
1
210
0
2
Order By: Relevance
“…Kalinowski et al reported that pro-forms of NRG-1 can be cleaved by TNF converting enzyme in response to the inflammatory cytokines IL-6 and IFN (18). Lemmens et al reported that mechanical strain increases endothelial NRG-1 synthesis and release, but angiotensin II and adrenergic agonists decrease endothelial NRG-1 synthesis and release (1,19).…”
Section: Discussionmentioning
confidence: 99%
“…Kalinowski et al reported that pro-forms of NRG-1 can be cleaved by TNF converting enzyme in response to the inflammatory cytokines IL-6 and IFN (18). Lemmens et al reported that mechanical strain increases endothelial NRG-1 synthesis and release, but angiotensin II and adrenergic agonists decrease endothelial NRG-1 synthesis and release (1,19).…”
Section: Discussionmentioning
confidence: 99%
“…Besides regulatory effects in the cardiovascular system, NRG-1 may have a more general physiological role, as suggested by the expression of NRG-1 and ErbB receptors in the central nervous system, liver, skeletal muscle, pulmonary cells, intestine, and kidney (5,9,20,33). With specific regard to the kidney, ErbB2, ErbB3, and ErbB4 are expressed in glomeruli and/or tubuli, with restricted expression of glomerular ErbB4 in mesangial cells (45).…”
mentioning
confidence: 99%
“…2,23,24 Among them, receptor tyrosine kinases can bind with epidermal growth factor, fibroblast growth factors, and neuregulin to activate several prohypertrophic signaling pathways, such as MAPK, AKT, and Ca 2+ dependent signaling. [25][26][27] Axl, a receptor of GAS6, is a member of the receptor tyrosine kinase family and has the highest expression level in heart and skeletal muscle, 28 which implies that it may play an important role in the pathophysiological process of heart disease. Intriguingly, the protein level of Axl was significantly higher in both myocardial biopsies and serum in patients with end-stage heart failure than in control heart donors.…”
Section: Discussionmentioning
confidence: 99%